Orthodontic Traction of Impacted Canine Using Cantilever - Nakandakari, Cláudia [UNESP]; Gonçalves, João Roberto [UNESP]; Cassano, Daniel Serra; Raveli, Taísa Boamorte [UNESP]; Bianchi, Jonas [UNESP]; Raveli, Dirceu Barnabé [UNESP] (Hindawi, 2016)
The impaction of the maxillary canines causes relevant aesthetic and functional problems. The multidisciplinary approach to the proper planning and execution of orthodontic traction of the element in question is essential. Many strategies are cited in the literature; among them is the good biomechanical control in order to avoid possible side effects. The aim of this paper is to present a case report in which a superior canine impacted by palatine was pulled out with the aid of the cantilever on the Segmented Arch Technique (SAT) concept. A 14.7-year-old female patient appeared at clinic complaining about the absence of the upper right permanent canine. The proposed treatment prioritized the traction of the upper right canine without changing the occlusion and aesthetics. For this, it only installed the upper fixed appliance (Roth with slot 0.018), opting for SAT in order to minimize unwanted side effects. The use of cantilever to the traction of the upper right canine has enabled an efficient and predictable outcome, because it is of statically determined mechanics.